2022 World Hypertension League, Resolve To Save Lives and International Society of Hypertension dietary sodium (salt) global call to action - Campbell, Norm R.C.; Whelton, Paul K.; Orias, Marcelo; Wainford, Richard D.; Cappuccio, Francesco P.; Ide, Nicole; Neal, Bruce; Chia, Yook Chin * (Springer Nature, 2022)
This fact sheet and global call to action is aimed at nutrition, hypertension, cardiovascular and other health care clinicians and scientists, and health advocates, as well as the organizations to which they belong. The ‘call’ is to align these audiences with the facts on: